Efektivitas Layanan Konseling Kelompok Dengan Teknik Self Instruction Untuk Mengurangi Stres Akademik Peserta Didik - Wasilah, Nurul (IJoCE: Indonesian Journal of Counseling and Education, 2024)
This study aims to determine the effectiveness of group counseling services using the self-instruction technique to reduce academic stress among students of SMA Negeri 4 PangkalPinang. This research employs a quantitative approach with an experimental method. The sample for this study was selected using purposive sampling techniques, with a total of 10 students exhibiting high levels of academic stress. In the data processing stage, raw scores were used, derived from calculations based on the Rasch model. The data collection technique employed in this study was an academic stress questionnaire modified from Gadzella's Student-Life Stress Inventory (SLSI). The method used for hypothesis testing was a paired sample t-test. Based on the results of the hypothesis test using the paired sample t-test, the obtained Ttable value was 2.262 and the Tstat value was 27.463, meaning Ttable < Tstat. Additionally, the Sig. (2-tailed) value was less than 0.05, specifically 0.000. The results of the paired sample t-test indicated a significant change before and after the intervention. Thus, it can be concluded that group counseling services using the self-instruction technique are effective in reducing academic stress among students of SMA Negeri 4 PangkalPinang.